Ethnic Prejudice in Children: The Role of Ethnic Socialization - Dyan Evita Santi; Suryanto Suryanto; M.G. Bagus Ani Putra (Journal of Educational, Health and Community Psychology, 2019)
AbstractThe study aims to examine the influence of parent’s ethnic socialization, peer’s ethnic socialization, and school climate on children’s ethnic prejudice. This research was conducted in 3 cities: Bangkalan, Yogyakarta, and Medan. The population of this study was 11-14-year-old children. The data was collected in Islamic and public schools. A total of 453 children were involved in this study, comprising of 173 children from Bangkalan, 132 children from Yogyakarta and 148 children from Medan. The result confirms the hypothesis that parents’ ethnic socialization has a negative influence on children's ethnic prejudice. If children perceive that their parent’s attempt to propagate ethnicity-related attitude becomes more intensive, then their ethnic prejudice will decrease accordingly. This research also proves that there is an insignificant negative effect of peers' ethnic socialization on children's ethnic prejudice. This means that the presence of peers’ ethnic socialization has no impact on children's ethnic prejudice. The study also finds an insignificant negative effect of school climate on children's ethnic prejudice. Further explanation of the result will be discussed in this article. Keywords: Ethnic prejudice, children in Indonesia, ethnic socialization